Declarative capacity does not trade-off with procedural capacity in children with specific language impairment. (October 2016) - Kuppuraj, Sengottuvel; Rao, Prema; Bishop, Dorothy VM
Background and aims: The procedural deficit hypothesis attributes the language phenotype in children with specific language impairment to an impaired procedural and relatively intact declarative memory system. The declarative compensatory hypothesis is an extension of the procedural deficit hypothesis which claims that the declarative system in specific language impairment compensates for the procedural deficit. The present study's aim was to examine the claims of the procedural deficit hypothesis and declarative compensatory hypothesis by examining these memory systems and relation between them in specific language impairment. Methods: Participants were children aged 8–13 years, 30 with specific language impairment and 30 typically developing controls, who spoke Kannada (an agglutinating language of the Dravidian family). Procedural learning was assessed using a serial reaction time task. Declarative memory was assessed using two non-verbal tasks that differed at the level of encoding and retrieval: a recognition memory task after incidental encoding using real and novel object images and a recall task after intentional encoding using visual paired associates. Retrieval was examined after short (10 min) and long (60 min) delays after encoding on both declarative tasks. Results: Findings confirmed that children with specific language impairment (SLI) have impaired procedural memory on a non-verbal serial reaction time task. On recognition memory task after incidental encoding though children with specific language impairment encoded less well, they recognized items as well as typically developing controls. Both the groups retrieved more at short compared to long intervals and retrieved real (verbalizable) objects better than novel objects. On visual paired associates (recall task with intentional encoding) children with specific language impairment retrieved less than typically developing children (even after controlling for non-verbal ability and age). Furthermore, across retrieval types of declarative tasks, although children with specific language impairment did less well than typically developing, their pattern of performance was comparable to typically developing children. Finally, the correlation between memory systems did not support a trade-off between memory systems in children with SLI as predicted by the compensatory wing of procedural deficit hypothesis. Conclusions: The findings supported the major claim of the procedural deficit hypothesis – a procedural learning deficit in specific language impairment and an intact declarative system, however, only if measured on task that was designed to be undemanding. Furthermore, there was no evidence for a trade-off between these systems. Implications and future directions: Some interventions with specific language impairment use explicit teaching of grammar, an approach that uses the declarative rather than the procedural system. Our findings cast doubt on whether this is likely to be the most effective strategy.